MALCOLM X'S PHILOSOPHY OF VIOLENCE: A PHILOSOPHICAL PARADIGM FOR SOCIAL LIBERATION OF THE BLACK RACE TOWARDS CONFLICT RESOLUTION, PEACE AND EQUALITY - Eyo Emmanuel Bassey; Ejesi Edwin C; Edor J. Edor (Universitas Negeri Makassar, 2020)
Malcolm X's advocacy of violence for the liberation of the black race in America has been a recondite and rare contribution in the paradigm of conflict resolution, peace and equality. the uniqueness of his proposal and reliance on violence in American social and political history has been hinged on unalterable conditions and creative restrictiveness upon which the black Americans were conscripted to live within this ambiance of dehumanized conditions. Malcolm X's philosophy was truly understood as a paradigm for struggle and revolutionary. Intentions for oppressed masses who were mainly blacks were traumatized by the actions and intentions of white American authorities. In this paper, we intend to show that Malcolm X's mission was to overcome the white American Supremacist tendencies and sermons were the black Americans who were continuously compelled to live within these enslaved conditions. And his vision was to create and extol black virtue, pence and equality in American society. Within these frames of his mission and vision, it is apparent that most times violence could be an assertive paradigm for conflict resolution, peace and equality of all human race